Gelidiella acerosa protects against Aβ 25-35-induced toxicity and memory impairment in Swiss Albino mice: an in vivo report - Syad Arif Nisha; Kasi Pandima Devi (Taylor & Francis Group, 2017)
Context: Alzheimer's disease (AD) is believed to develop due to deposition of β-amyloid (Aβ) peptide. Hence, efforts are being made to develop potent drug that target amyloid hypothesis. Objective: The present study explores the effect of the seaweed Gelidiella acerosa (Forsskål) Feldmann & Hamel (Gelidiellaceae) against Aβ 25-35 peptide in Swiss albino mice. Materials and methods: The animals were administered through intracerebroventricular (ICV) injection with the Aβ 25-35 peptide (10 μg/10 μL/ICV site) on 21st day of the pretreatment of G. acerosa (whole plant) benzene extract (200 and 400 mg/kg bw). On day 30, animals were sacrificed and brain tissue homogenate was prepared. The activities of AChE, BuChE, b-secretase, MAO-B, and caspase-3 were determined, and Bax expression was assessed by Western blotting. Results: Gelidiella acerosa benzene extract restored the level of antioxidant enzymes and prevented lipid and protein oxidation significantly (p < 0.05). The extract protected the mice from cholinergic deficit significantly (p < 0.05) by inhibiting the activities of AChE and BuChE, which was about 0.116 ± 0.0088 U/mg of protein and 0.011 ± 0.0014 U/mg of protein respectively, which was otherwise increased in peptide-treated group (0.155 ± 0.007 U/mg of protein and 0.015 ± 0.0012 U/mg of protein respectively). Interestingly, G. acerosa benzene extract inhibited β-secretase and MAO-B activity. Reduction (p < 0.05) in level of caspase-3 activity and Bax expression suggests that G. acerosa protects the cells from apoptosis. Discussion and conclusion: The results suggest that G. acerosa possesses excellent neuroprotective potential against peptide mediated toxicity under in vivo conditions.